Diastereo- and enantioselective direct vinylogous Michael addition of γ-substituted butenolides to 2-enoylpyridines catalyzed by chiral bifunctional amine-squaramides. Issue 87 (15th September 2015) - Wang, Zhen-Hua; Wu, Zhi-Jun; Huang, Xue-Qun; Yue, Deng-Feng; You, Yong; Xu, Xiao-Ying; Zhang, Xiao-Mei; Yuan, Wei-Cheng
Abstract : The enantioselective vinylogous Michael addition of γ-substituted butenolides to 2-enoylpyridines was developed to yield γ, γ-disubstituted butenolide derivatives in excellent stereoselectivities. Abstract : The diastereo- and enantioselective direct vinylogous Michael addition reaction of γ-substituted butenolides to 2-enoylpyridines has been achieved. A range of γ, γ-disubstituted butenolide derivatives, bearing two consecutive tri- and tetrasubstituted stereogenic centers, were readily obtained in good yields with excellent stereoselectivities (up to >99 : 1 dr and >99% ee).